2023
DOI: 10.3390/ijms241713158
|View full text |Cite
|
Sign up to set email alerts
|

Glutaryl-CoA Dehydrogenase Misfolding in Glutaric Acidemia Type 1

Madalena Barroso,
Marcus Gertzen,
Alexandra F. Puchwein-Schwepcke
et al.

Abstract: Glutaric acidemia type 1 (GA1) is a neurotoxic metabolic disorder due to glutaryl-CoA dehydrogenase (GCDH) deficiency. The high number of missense variants associated with the disease and their impact on GCDH activity suggest that disturbed protein conformation can affect the biochemical phenotype. We aimed to elucidate the molecular basis of protein loss of function in GA1 by performing a parallel analysis in a large panel of GCDH missense variants using different biochemical and biophysical methodologies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The crystal structure of human GCDH complexed with alternate substrate 4-nitrobutyryl-CoA has been determined and is available in the Research Collaboratory for Structural Bioinformatics Protein Data Bank (PDB) (PDB code: 1SIR) [32]. Several studies used this model to investigate potential effects of GCDH missense variants on protein folding and stability, encompassing novel variants identified in a patient as well as large sets of already known variants and genotypes [12,28,29,44,45]. A consistent assessment of these results is challenging because different approaches were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of human GCDH complexed with alternate substrate 4-nitrobutyryl-CoA has been determined and is available in the Research Collaboratory for Structural Bioinformatics Protein Data Bank (PDB) (PDB code: 1SIR) [32]. Several studies used this model to investigate potential effects of GCDH missense variants on protein folding and stability, encompassing novel variants identified in a patient as well as large sets of already known variants and genotypes [12,28,29,44,45]. A consistent assessment of these results is challenging because different approaches were used.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple investigators performed in vitro GCDH enzyme activity analysis in heterologous cells (E. coli or COS-7) [9,11,27]. Furthermore, a considerable number of studies addressed the additional potential impact of missense variants on GCDH function [28][29][30][31][32]. Thus, PS3 was used as supporting evidence from functional studies (PS3_Supporting) if only one study showed a residual mutant enzyme activity of 0-50% measured in vitro in comparison to the wild-type enzyme activity.…”
Section: Functional Datamentioning
confidence: 99%